IDIOMATIC EXPRESSIONS AND THEIR INDONESIAN SUBTITLES IN THE GOOD DOCTOR TV SERIES - Tyasrinestu, Patricia; Ardi, Priyatno (LLT Journal: A Journal on Language and Language Teaching, 2020)
Idiomatic expressions are used to describe things or conditions that cannot be described by plain words. They carry more impacts than non-idiomatic expressions due to their close identification with a particular language and culture. This research investigates idiomatic expressions and their Indonesian subtitles in The Good Doctor TV series. Two research questions are addressed in this study, namely (1) what types of idiomatic expressions are found in The Good Doctor TV series? and (2) how are the idiomatic expressions in the TV series translated into Indonesian? The researchers employed content analysis. The steps of data collection and analysis included taking the transcript and identifying the idiomatic expressions, identifying their meanings and validating them, and comparing the meanings of the two idiomatic expressions. The results revealed that, first, The Good Doctor TV series contained five types of idiomatic expressions, namely substitutes, proper names, English phrasal compound, figure of speech, and slang. Abbreviation was not found in the TV series. Second, there existed six translation strategies to translate idiomatic expressions in English into Indonesian.DOI: doi.org/10.24071/llt.2020.230104